Analisis Penilaian Karakter Berbasis Asesmen Kompetensi Madrasah Indonesia (AKMI) - Yusrianum Yusrianum; Nurmawati Nurmawati (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2022)
Through education, humans can develop and advance their potential to become human beings who have the ability to face the era of globalization that demands expertise and abilities in all areas of life. The Indonesian Madrasah Competency Assessment (AKMI) is the latest program owned by the Ministry of Religious Affairs of the Republic of Indonesia, where AKMI is one of the evaluation tools for students. This study aims to analyze character assessment Character education based on Islam means character education whose components include moral knowledge, feelings about morals, and moral deeds. These morals are explored and developed based on Islamic values. The application of character education aims to shape the character of students who are Islamic and tolerant. This article uses the literature study method or what is commonly called a literature study. This research was conducted by collecting data from various references through several books, magazines related to the aim of revealing various theories related to the problem being faced or studied. The results showed that the Indonesian Madrasah Competency Assessment (AKMI) test can provide a clear diagnosis of students' abilities in school.